2008
DOI: 10.1016/j.neuroscience.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise or amphetamine treatment, but not the combination, increases hippocampal brain-derived neurotrophic factor and synapsin I following cortical contusion injury in rats

Abstract: Prior work has shown that d-amphetamine (AMPH) treatment or voluntary exercise improves cognitive functions after traumatic brain injury (TBI). In addition, voluntary exercise increases levels of brain-derived neurotrophic factor (BDNF). The current study was conducted to determine how AMPH and exercise treatments, either alone or in combination, affect molecular events that may underlie recovery following controlled cortical impact (CCI) injury in rats. We also determined if these treatments reduced injury-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 82 publications
3
65
1
1
Order By: Relevance
“…First, co-administration of the two therapies did not negate the benefits induced by one or both treatments, as has been reported with other dual-treatment strategies (Faden, 1993;Griesbach et al, 2008;Guluma et al, 1999;Kline et al, 2002a). Second, both EE groups performed significantly better in the water maze versus the STD-housed groups on the first day of training (day 14 post-TBI), despite no difference in the acute neurological assessments that are correlated with injury severity.…”
Section: Figsupporting
confidence: 52%
“…First, co-administration of the two therapies did not negate the benefits induced by one or both treatments, as has been reported with other dual-treatment strategies (Faden, 1993;Griesbach et al, 2008;Guluma et al, 1999;Kline et al, 2002a). Second, both EE groups performed significantly better in the water maze versus the STD-housed groups on the first day of training (day 14 post-TBI), despite no difference in the acute neurological assessments that are correlated with injury severity.…”
Section: Figsupporting
confidence: 52%
“…In the course of this knowledge and experience, it has been shown that regularly exercising animals and people are receiving responses to improving endurance capacity by reducing oxidant production and increasing antioxidant defense mechanisms and mitochondrial biogenesis [34,35]. Therefore, they are the neuroprotective effects of aerobic exercise training [36,37]. In addition, exercise also increases the expression and levels of neurotrophic and growth factors such as Insulin-like growth factor 1, fibroblast growth factor 2 and brain-derived neurotrophic factor [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…(16) Brain-derived neurotrophic factor Brain-derived neurotrophic factor (BDNF is a key molecule for neuroplasticity. (36) It is expressed in many cell types, including neurons and glia cells. Increased expression of BDNF in the central nervous system, in response to various stimuli, suggests a neuroprotector role for this neurotrophine.…”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 99%
“…In TBI, experimental studies in rates disclosed an increased RNAm of BDNF in the hippocampus within the first 24 hours following trauma. (36) Thereupon we studied the serum levels of BDNF patients, victims of severe TBI. We found high serum levels of BDNF in the first hours after TBI, with a correlation of the serum levels of BDNF and fatal outcome in patients with isolated severe TBI.…”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 99%
See 1 more Smart Citation